2022
DOI: 10.2138/am-2022-8051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fluorine on the thermal stability of phlogopite

Abstract: Knowledge of volatile cycling is vital to understand evolution of the planet and the life it supports. Although it is gradually accepted that the mantle is a vast store house of H 2 O and other volatiles, the impact of co-existing volatiles on the thermal stabilities of OH and the lattice of the host mineral is still poorly understood.Phlogopite is one of the few hydrous minerals capable of carrying both water and halogens into the mantle. Previous observations from both experiments and textural relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…Assuming that the effects of F on thermal stability are approximately linear, consistent with in situ observations at ambient pressures reported by Sun et al. (2022), the thermal stability could be increased by as much as ∼222 and ∼445°C for phlogopite containing 4 and 8 wt.%, respectively. Note that an approximately linear dependency of phlogopite thermal stability with F content is also consistent with the observations for simplistic natural systems obtained at 0.7–2.8 GPa (Dooley & Patiño Douce, 1996; Foley et al., 1986a; Hensen & Osanai, 1994).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…Assuming that the effects of F on thermal stability are approximately linear, consistent with in situ observations at ambient pressures reported by Sun et al. (2022), the thermal stability could be increased by as much as ∼222 and ∼445°C for phlogopite containing 4 and 8 wt.%, respectively. Note that an approximately linear dependency of phlogopite thermal stability with F content is also consistent with the observations for simplistic natural systems obtained at 0.7–2.8 GPa (Dooley & Patiño Douce, 1996; Foley et al., 1986a; Hensen & Osanai, 1994).…”
Section: Resultssupporting
confidence: 89%
“…Previous studies have shown that phlogopite from peridotitic xenoliths can contain up to 8 wt.% F (Liu et al, 2011), with examples from Sicily, Italy (Gianfagna et al, 2007) and Namalulu, Tanzania (Feneyrol et al, 2012) (see also Figure S1 in Supporting Information S1). Assuming that the effects of F on thermal stability are approximately linear, consistent with in situ observations at ambient pressures reported by Sun et al (2022), the thermal stability could be increased by as much as ∼222 and ∼445°C for phlogopite containing 4 and 8 wt.%, respectively. Note that an approximately linear dependency of phlogopite thermal stability with F content is also consistent with the observations for simplistic natural systems obtained at 0.7-2.8 GPa (Dooley & Patiño Douce, 1996;Foley et al, 1986a;Hensen & Osanai, 1994).…”
Section: Quantification Of the Effects Of F On K-richterite And Phlog...supporting
confidence: 85%
See 3 more Smart Citations